The MAK‐Collection for Occupational Health and Safety 2018
DOI: 10.1002/3527600418.mb6417e6518
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol [MAK Value Documentation, 2018]

Abstract: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated the maximum concentration at the work place (MAK value) and the Pregnancy Risk Group of ethanol [ 64‐17‐5 ]. Ethanol is produced endogenously. Uptake of greater amounts depresses the central nervous system and is carcinogenic especially for the liver. The former MAK value of 500 ml/m 3 was derived from a study in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…JEFCA concluded that the use of ethanol as an extraction solvent should be restricted to usage determined by good manufacturing practice, in which case residues are unlikely to have any toxicological effects and that ethanol posed no safety concern at the levels of intake resulting from use of ethyl esters as flavouring agents (JEFCA 1970). The German Research Foundation (DFG) MAK commission has rated ethanol and acetaldehyde as class 5 carcinogens (Hartwig and MAK commission 2018). This class comprises compounds that cause or are considered to cause cancer in humans or animals for which a MAK value can be derived.…”
Section: Characterisation Formation Occurrence and Public Health Conc...mentioning
confidence: 99%
See 1 more Smart Citation
“…JEFCA concluded that the use of ethanol as an extraction solvent should be restricted to usage determined by good manufacturing practice, in which case residues are unlikely to have any toxicological effects and that ethanol posed no safety concern at the levels of intake resulting from use of ethyl esters as flavouring agents (JEFCA 1970). The German Research Foundation (DFG) MAK commission has rated ethanol and acetaldehyde as class 5 carcinogens (Hartwig and MAK commission 2018). This class comprises compounds that cause or are considered to cause cancer in humans or animals for which a MAK value can be derived.…”
Section: Characterisation Formation Occurrence and Public Health Conc...mentioning
confidence: 99%
“…The same committee further calculated an additional breast cancer risk of 4/10 3 after 40 years exposure towards 1300 mg/m 3 . In addition, the German MAK commission considered thatbased on the variation of the endogenous exposure-an occupational exposure of 200 mL/m 3 (380 mg/m 3 ) would be within the standard deviation of the lifetime AUC and thus would contribute only little to the cancer risk (Hartwig and MAK commission 2018).…”
Section: Impact Of Endogenous Formation On Risk Assessmentmentioning
confidence: 99%